Digital Impression - Begum, Aleya; Ahmed, Rubaba; Islam, Md Saiful (City Dental College Journal, 2012)
The use of different impression materials is in vogue for last few years with a view of capturing more accurate dental impression, which in turn produces more accurate fitting restoration. For achieving this goal, one should have ample knowledge about the different physical and mechanical properties, as well as in different techniques with the most recent advances. In this review, we highlighted the impression material and recent updates on Digital Dentistry with the benefits which can be gained from this system by both Clinician and Dentist. DOI: http://dx.doi.org/10.3329/cdcj.v9i2.12321 City Dental College J. Volume-9, Number-2, July-2012